Doświadczenie wegetarianizmu w okresie dorastania i wczesnej dorosłości = Experience of vegetarianism during adolescence and early adulthood - Brzezińska, Adrianna (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The aim of the study was to explore the reasons why young people choose a vegetarian diet during adolescence and early adulthood. The study was conducted using the case study method, involving autobiographical and narrative interviews with seven individuals who had adopted a vegetarian diet before the age of 18 and were continuing to do so at the time of the study.
Keywords: vegetarianism; vegetarian diets; academic youth; adolescence; motive; wegetarianizm; diety wegetariańskie; młodzież akademicka; adolescencja; motyw